2011
DOI: 10.1016/j.conbuildmat.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A study on the mechanical behaviour of cement–bitumen treated materials

Abstract: The hardmetal cutting tools used in machining are submitted to extreme conditions in terms of temperature and mechanical loading. A better understanding of the failure of cutting tools and capability to predict tool life are key factors in the development of new tool materials with improved mechanical behaviour. Main failure mechanisms are wear, thermal-mechanical fatigue and brittle fracture. The aim of present work is to study the mechanical behaviour of two hardmetals. The properties studied were Young's mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 30 publications
2
57
0
5
Order By: Relevance
“…The higher the α value, the more temperature sensitive the material. The results are comparable with those published by other authors (Pasetto and Baldo 2010, Bocci et al 2011, Grilli et al 2012.…”
Section: Figure 8 Stiffness Modulus Of Cbems At 28 Days Under Differesupporting
confidence: 83%
See 2 more Smart Citations
“…The higher the α value, the more temperature sensitive the material. The results are comparable with those published by other authors (Pasetto and Baldo 2010, Bocci et al 2011, Grilli et al 2012.…”
Section: Figure 8 Stiffness Modulus Of Cbems At 28 Days Under Differesupporting
confidence: 83%
“…At the end of the reaction of the GGBS and FA, and Ca(OH)2, new hydration products, such as C-S-H gel, is formed (Oner and Akyuz 2007). Table 6 presents model (2) parameters fitting, which has been used to describe the increase of stiffness in CAM (Bocci et al 2011); test fit curves are shown in Figure 6.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A recent development aimed at achieving excellent engineering properties of CAMs is the use of manufactured fillers. This kind of filler is produced as a blend of reactive, semi-reactive and non-reactive natural fillers [6,7,13,14]. In this study, binary blended fillers (BBFs) contain a combination of fly ash (FA) or granulated blast furnace slag (GGBS) with ordinary Portland cement (OPC), while the ternary blended fillers (TBFs) are a combination of BBFs with silica fume (SF).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the addition of cement increases strength and stiffness as well as permanent deformation resistance (Du 2014;Grilli et al 2012). Whereas, the presence of bitumen amongst the recycled aggregate affects cohesion, durability and fatigue cracking resistance and reduced moisture sensitivity of the mixture as well (Bocci et al 2011). In addition, the visco-elastic behavior and temperature dependency of the bituminous binder confers to CBTM asphalt-like properties (Cardone et al 2014;Grilli et al 2012).…”
Section: Introductionmentioning
confidence: 98%